2020
DOI: 10.1177/0954008319897745
|View full text |Cite
|
Sign up to set email alerts
|

Optimized synthesis of isocyanate microcapsules for self-healing application in epoxy composites

Abstract: Microcapsules containing isophorone diisocyanate were fabricated in oil-in-water emulsion. The emulsification effect of different emulsifiers during the capsule synthesis was systematically investigated by optical microscope. Three kinds of shell materials were discussed to obtain the high core content, smooth-surfaced, and robust capsule by scanning electronic microscope and Fourier transform infrared spectroscopy. Self-healing performance of corresponding self-healing epoxy composites was fully evaluated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…However, GA is composed of arabinogalactan (88.4%), arabinogalactan protein (10.4%), and glycoprotein (1.24%), and its emulsifying property is mainly attributed to arabinogalactan protein, which is the reason for the high amounts needed to reach a stable emulsion [ 8 , 9 ]. Studies report on the optimization of the GA concentration targeting the control of the MCs’ morphology, size, and size distribution [ 10 , 11 , 12 ]. It was observed that as the GA concentration increases, the sphericity and uniformity of the MCs improve.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, GA is composed of arabinogalactan (88.4%), arabinogalactan protein (10.4%), and glycoprotein (1.24%), and its emulsifying property is mainly attributed to arabinogalactan protein, which is the reason for the high amounts needed to reach a stable emulsion [ 8 , 9 ]. Studies report on the optimization of the GA concentration targeting the control of the MCs’ morphology, size, and size distribution [ 10 , 11 , 12 ]. It was observed that as the GA concentration increases, the sphericity and uniformity of the MCs improve.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that as the GA concentration increases, the sphericity and uniformity of the MCs improve. However, it is only for concentrations of GA above 12 wt% that a significant reduction in the MCs size occurs, which is correlated with a considerable increase in the continuous phase viscosity [ 10 , 11 , 12 ]. Examples of other stabilizers reported in the literature for this application are Tween 80, Tween 20, Sodium dodecyl sulfate (SDS), SPAN20, polyvinyl alcohol (PVA), dodecyl benzene sulfonate (SDBS), and combinations of GA with CTAB (cetrimonium bromide) and PVA with SDS [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1999, Zako et al 46 added small thermoplastic particles to thermosetting materials (glass fiber/epoxy composites), which melted upon heating, thus repairing the damaged cracks. They also confirmed that the addition of F I G U R E 5 A general mechanism to a typical ROMP reaction 35 Isophorone diisocyanate -polymerization reaction 86% 43 small thermoplastic particles did not reduce the strength of the thermosetting glass fiber composite. This technology enables the use of up to 40% thermoplastic adhesives in glass fiber reinforced epoxy composites.…”
Section: Thermoplastic Additivesmentioning
confidence: 56%
“…15 The most preferred method is to use microcapsules as containers for the healing agent and activator. Amine, 16 polydimethylsiloxane, 17 isophorone diisocyanate, 18 epoxy, 16,19 sodium monofluorophosphate 14 and PU resin [20][21][22][23][24][25] are among the materials used. Self-healing microcapsules are incorporated into the materials to repair damage or a crack.…”
Section: Introductionmentioning
confidence: 99%